Evaluasi Financial Distress PT Lippo Karawaci Tbk Melalui Metode Altman Z-Score Selama Fase Pemulihan Ekonomi 2022–2024 - Andreanus Halim Saputra; Dalizanolo Hulu (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The post-pandemic recovery of Indonesia’s property sector occurs amid global economic pressures, making it crucial to assess the financial distress risk of major developers such as PT Lippo Karawaci Tbk. This study aims to evaluate the company’s financial health during 2022–2024 using the Altman Z-Score model through a quantitative descriptive approach based on secondary financial data. The results show an improvement in the Z-Score from the Distress Zone in 2022 (0.584) and 2023 (0.901) to the Grey Area in 2024 (2.374). However, this increase is largely driven by non-operational income, while core operational performance declined. The study concludes that the observed improvement does not reflect a fundamental recovery, and future research should separate non-operational income effects and incorporate macroeconomic variables for a more comprehensive assessment.